2017
DOI: 10.1016/j.heliyon.2017.e00326
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum genotypes in matched peripheral, placental and umbilical cord blood in an area characterised by unstable malaria transmission in eastern Sudan

Abstract: BackgroundThere are few published studies on Plasmodium falciparum genotypes in peripheral, placental and umbilical cord blood in areas characterised by unstable malaria transmission.MethodA cross-sectional study was conducted to investigate P. falciparum genotypes in matched peripheral, placental and umbilical cord blood in eastern Sudan. Thick blood smears and P. falciparum merozoite surface protein 1 (MSP1) and 2 (MSP2) genes as polymorphic markers in polymerase chain reactions were investigated in 3 kinds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
4
3
3
Order By: Relevance
“…The present study showed no association between the submicroscopic parasitaemia and age and parity. This is consistent with previous studies performed in an area of unstable malaria transmission in Eastern Sudan [21, 25]. Likewise, age and parity were not associated with submicroscopic malaria in an area with intense malaria transmission in Gabon [29], and in Cameron and Malawi [11, 30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study showed no association between the submicroscopic parasitaemia and age and parity. This is consistent with previous studies performed in an area of unstable malaria transmission in Eastern Sudan [21, 25]. Likewise, age and parity were not associated with submicroscopic malaria in an area with intense malaria transmission in Gabon [29], and in Cameron and Malawi [11, 30].…”
Section: Discussionsupporting
confidence: 91%
“…falciparum infections ( P < 0.001). This finding is in line with the previous studies in Sudan on the frequency of submicroscopic infection in the three compartments [12, 25]. Other reports described submicroscopic parasitaemia in different geographical areas and in a systemic review carried out in Africa; the weighted mean of submicroscopic infection was 36% [16].…”
Section: Discussionsupporting
confidence: 91%
“…The 3D7/MSP2 allele was predominant such as reported in the previous report in the same site (Francine et al, 2016). Similar results are observed in Senegal (Jafari-Guemouri et al, 2005), Sudan (Fadlelseed et al, 2017). In Gabon, the predominant allele was FC27/MSP2 (Kassberger et al, 2002, Mayengue et al, 2004.…”
Section: Discussionsupporting
confidence: 89%
“…Several previous studies on the antigenic diversity of P. falciparum matched in peripheral, placental and umbilical cord blood have shown varied results in different country. Some studies have shown a parasitic overlap found for each of these compartments while others have revealed a subpopulation of peripheral parasites sequestered in the placenta (Kassberger et al, 2002;Mayengue et al, 2004;Fadlelseed et al, 2017;Guitard et al, 2010;Cohee et al, 2016). Recent published work conducted in the same area reported 29 MSP-2 alleles in isolates from peripheral blood of pregnant women with asymptomatic P. falciparum infection at antenatal visits, suggesting a wide diversity of the P. falciparum population (Francine et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The msp1 type genes were more diverse in peripheral blood compared to placental and cord blood. This data are different from those reported in Sudanese women, showing higher diversity of the gene in the placental blood compartment [ 37 ], but confirm the previous findings suggesting that the profile of P. falciparum strains circulating in the peripheral blood of pregnant women might differ from that found in the placental and cord blood. Previous studies from high malaria transmission settings have reported several strains of P. falciparum circulating in pregnant women among which some were more prevalent in the placental blood in comparison to peripheral blood compartment.…”
Section: Discussioncontrasting
confidence: 83%